Lagenorhynchus acutus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lagenorhynchus acutus (Gray 1828) [Delphinus] acutus Gray 1828, Spicil. Zool., 1: 2. Type Locality: None given, listed as North Sea, Faeroe Isls (Denmark) (uncertain) by Gray (1846:36). Vernacular Names: Atlantic White-sided Dolphin. Synonyms: Lagenorhynchus gubernator Cope 1876; Lagenorhynchus leucopleurus (Rasch 1843); Lagenorhynchus perspicillatus Cope 1876. Distribution: North Atlantic: cold temperate waters; L. acutus tends to be distributed to the south of L. albirostris . Conservation: CITES – Appendix II; IUCN – Lower Risk (lc). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 729, DOI: 10.5281/zenodo.7316519